Pengaruh Implementasi Sistem Informasi Manajemen Keuangan Daerah (Simda), Kualitas Sumber Daya Manusia, Dan Dukungan Manajemen Puncak Terhadap Kualitas Laporan Keuangan Daerah(Penelitian pada Pemerintah Kabupaten Tegal) - Alfiani, Nur, Drs. Atwal Arifin, M.Si., Akt, CA (2017)
The government is obliged to make financial reports as a tool of control, job evaluation, as one of accountability and as a basis for decision making. The financial statements of the government is good according to Government Regulation No. 71 of 2010 should include the four characteristics that is relevant, reliable, comparable, and understandable.This study aims to determine the effect of SIMDA implementation, quality of human resources and support of top management in the quality of local goverment's financial statements. The study population at the SKPD Tegal regency. The sample in this study amounted to 54 respondents using a sampling technique is purposive sampling. Data was analyzed by using multiple linear regression.The results of this study indicate that the SIMDA implementation and quality of human resources affects the quality of local government financial reports because it has significant value less than 0.05. While top management support does not affect the quality of local government financial reports because it has a value significantly greater than 0.05. Keywords: Quality of financial statements, SIMDA implementation, quality of human resources, top management support.